EXPLORATORY STUDY OF VIDEO COLLECTION BROWSING BEHAVIOUR OF PATRONS IN AN ACADEMIC LIBRARY - M. Yasser, Chuttur (Malaysian Journal of Library and Information Science, 2017)
Previous studies on browsing have mostly focused on print materials and websites. The presentresearch investigates the browsing behaviour of patrons when interacting with video collections. Using non-participant observation method, 22 patrons were observed browsing video collections in a large Midwestern university library over a period of three days with each observation lasting for an hour. To supplement some of the observations made, four of the observed participants were also interviewed. Observations show that when compared to previously reported findings on browsing behaviour of patrons with print materials and websites, the same browsing patterns seem to emerge when individuals interact with video collections. In addition, this study reveals that patrons frequently showed feelings of frustrations when it came to selecting a video. One possible reason could be the lack of information available to patrons for helping them in their decision making process. Further studies are, however, required to substantiate this claim.